2003
DOI: 10.1289/ehp.5812
|View full text |Cite
|
Sign up to set email alerts
|

Protein digestibility and relevance to allergenicity.

Abstract: In January 2001 a Joint Food and Agriculture Organization of the United Nations/World Health Organization Expert Consultation Committee on Allergenicity of Foods Derived from Biotechnology published a report outlining in detail an approach for assessing the allergenic potential of novel proteins. One component of this decision tree is a determination of whether the protein of interest is resistant to proteolytic digestion. Although these (Italic)in vitro(/Italic) methodologies have been useful, the correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…The relationship of the resistance to digestion and the likelihood a dietary protein is an allergen was identified (Astw ood 1996;Vassilopoulou 2006;Moreno 2005;Vieths, 1999) but the assay was never meant to mimic the fate of proteins in vivo and the correlation is not absolute (Fu 2000). Rath er, the assay was meant to identify proteins that share a physico-chemical property, resistance to digestion, of known food allergens (Bannon 2004). The purpose is to provide information that, in conjuncti on with other evidence, would be useful in predicting whether a dietary protein may become a food allergen (Bannon 2003).…”
Section: General Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship of the resistance to digestion and the likelihood a dietary protein is an allergen was identified (Astw ood 1996;Vassilopoulou 2006;Moreno 2005;Vieths, 1999) but the assay was never meant to mimic the fate of proteins in vivo and the correlation is not absolute (Fu 2000). Rath er, the assay was meant to identify proteins that share a physico-chemical property, resistance to digestion, of known food allergens (Bannon 2004). The purpose is to provide information that, in conjuncti on with other evidence, would be useful in predicting whether a dietary protein may become a food allergen (Bannon 2003).…”
Section: General Conclusionmentioning
confidence: 99%
“…Rath er, the assay was meant to identify proteins that share a physico-chemical property, resistance to digestion, of known food allergens (Bannon 2004). The purpose is to provide information that, in conjuncti on with other evidence, would be useful in predicting whether a dietary protein may become a food allergen (Bannon 2003). Therefore, we do not agree that there is value to in vitro digestibility assays performed under more physiological conditions to account for individuals with altered digestive physiology.…”
Section: General Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations have indicated that there exists an association between the resistance of proteins to digestion in a simulated gastric fluid and sensitizing activity . Although this correlation is not absolute, evaluation of resistance to proteolysis is currently regarded as one component of the safety assessment process (Bannon et al 2003). It is frequently assumed that such an association reflects the fact that for a protein to induce sensitization after oral ingestion, it will have to display some level of stability in the gastric environment in order to interact effectively with the mucosal immune system.…”
Section: Oral and Systemic Exposure Of Balb/c Micementioning
confidence: 99%
“…Several investigators term protein as «stable» after incubation times ranging from 8 to 60 min (Bannon et al 2003;Fu 2002;Herman et al 2006). As far as the unstable proteins usually survive less than 15 sec in the similar assay conditions, such conclusion seems to be quite correct.…”
mentioning
confidence: 99%